Laços luso-paraense na imprensa oitocentista - TAVARES, Maria Lucilena Gonzaga Costa (Universidade Federal do Pará, 2019)
Almost two centuries of the independence of Brazil, some ties still linger in Pará, beyond the language and the political and cultural history left by the Portuguese colonizers. Thus, it was up to the newspaper to archive part of this important story that, in some Brazilian provinces, also witnessed harsh prospects of what intended Brazilians, as happened in Grand Pará Province, whose peculiarity focuses even before his "adherence" to independence in 1823. Therefore, we investigated some newspapers of Pará from the nineteenth century, in particular, those of the 1840s - respectively the end of Cabanagem - the 1880, the decline of Romanticism, in order to show from the perspective of literary history, such as the Grand Province - witnessed in adverse direction of the other, the lusophilia and permanence of Portuguese culture. We propose as the source the journals from Pará cataloged in the microfilm sector from Arthur Viana library, located in the Cultural Foundation of Pará, in which we find record keeping existing literary ties between Brazil and Portugal in the nineteenth century. This research will serve as a bibliographic source to those interested in historical and cultural relationship between Pará and Portugal, given that mosto of the newspapers investigated is located solely in the said Para state library, which certainly favors the little publicity about this historiographical content, besides placing Pará among the important Brazilian provinces of the nineteenth century.